Risk issues of software and IT outsourcing and its impact on business continuity - O'Connor, Rory V. (Henry Stewart Talks, 2011)
Software Acquisition, Build versus Buy, Outsourcing, Inshore, nearshore, offshore, Risk Management business continuity planning, Outsourcing and Risk, Common outsourcing risks, Managing outsourcing Risks, Outsourcing Risk mitigation, Outsourcing Critical Success Factors